HUBUNGAN KARAKTERISTIK DAN VAGINAL DOUCHING DENGAN KEJADIAN IMS - Kumalasari Kumalasari (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2019)
Increasing InsidensSTI and spread arround the word cannot be expected exactly. STI doesn’t from base factors which are transmitted by changing sexual partner, unsequere sexual mobility, prostitute less knowledge about hygiene genetalia, and dynamic factor that happened in the society, that cause reproduvtive and sexuall problem infected especial married women, children and poor. PHC Bandarharjo has high rate case with STI so cases in 2014 and 90% is married women. The aim of this research is to prove the relationbetween characteristicsand vaginal douching with STI.This research used with case control study design, 80 sampels with 1:1 (40 respondents each group), in PHC Bandarharjo working area. The case is married women who had positive STI and the control is married women who had negative STI after checked fisicly and confirm laboratorium in PHC Bandarharjo. The data is analyzed with univariat and bivariate (chi-squere).Some factors that proven affect STI for married women is a vagina douching (OR=11; 95% CI 3,8-31,7; p=0,000,low income family(OR= 4,0 95%CI :1,6-11 p= 0,004), there is relation between STI with married women that vaginal douching, and relation between STI with married women low income family.